MAKNA SAPATHA PADA PRASASTI SUKAWANA - I Wayan Sumerata (Forum Arkeologi, 2016)
Weak social control in the past caused the king issued sapatha which listed in an inscription. This research aims to reveal the meaning of sapatha and the elements which influence it. Therefore, understanding of sapatha will be known overall and understood by people especially those who inherited it. Data were collected through observation, direct reading, and literature study related to inscription researches in Kintamani area. The data were analyzed based on inscription analysis technic with some steps namely source identification through transliteration and translation. Data interpretation was done by generally describing groups of inscription which contain sapatha and presented descriptive-qualitatively. Groups of Sukawana Inscription which contain sapatha are inscriptions of Sukawana AII which was issued by King Anak Wungsu dated from 976 Saka or 1054 A.D and Sukawana D which was issued by King Patih Kebo Parud. Sapatha is a social control which contains several meanings namely power, religion, and law. Those meanings show the greatness of the power domination in any interest. Kontrol sosial yang sangat lemah pada masa lalu menyebabkan raja mengeluarkan sapatha yang dicantumkan dalam sebuah prasasti. Penelitian ini bertujuan untuk memahami makna yang terkandung dalam sapatha dan unsur-unsur yang mempengaruhinya. Dengan demikian pemahaman terhadap sapatha akan diketahui secara menyeluruh dan dapat memberikan pengertian terhadap masyarakat, khususnya masyarakat yang mewarisinya. Tahap pengumpulan data dilakukan melalui pengamatan dan pembacaan langsung, serta studi kepustakaan terhadap berbagai literatur yang berkaitan dengan penelitian prasasti di wilayah Kintamani. Tahap analisis data dilakukan berdasarkan teknik analisis prasasti dengan tahapan seperti identifikasi sumber melalui alih aksara dan alih bahasa. Tahap penafsiran data dilakukan dengan memaparkan isi secara umum kelompok Prasasti yang memuat tentang sapatha, dan disajikan secara deskriptifkualitatif. Kelompok Prasasti Sukawana yang memuat tentang sapatha adalah prasasti Sukawana AII yang dikeluarkan oleh raja Anak Wungsu berangka tahun 976 Saka atau 1054 dan prasasti Sukawana D yang dikeluarkan oleh Raja Patih Kebo Parud. Sapatha merupakan sebuah kontrol sosial yang mengandung beberapa makna seperti makna kekuasaan, religi, dan hukum. Semua makna tersebut menunjukkan besarnya dominasi kekuasaan dalam bebagai kepentingan.